Development of village-owned enterprise organizations (BUMDES) in North Minahasa regency, North Sulawesi province - Mardani Setiawan; Fernandes Simangunsong; Layla Kurniawati (Jurnal Scientia, 2024)
The purpose of this research is to determine and analyze the Organizational Development of Village-Owned Enterprises (BUMDes), determine and analyze the supporting and inhibiting factors for the Organizational Development of Village-Owned Enterprises, as well as determine and analyze efforts to overcome the factors inhibiting the Organizational Development of Village-Owned Enterprises in Minahasa Regency North of North Sulawesi Province. The theory used as an analytical tool in writing this thesis is the theory from Gouillart and Kelly in Simangunsong (2014) which explains that Organizational Development requires 4 (four) stages (known as the 4 R model) for organizational renewal, namely "Reframing, Restructuring , Revitalization, and Renewal”. The method used is a qualitative approach with data collection techniques, namely interviews, observation, documentation and data triangulation. The informants in this research were the Deputy Regent of North Minahasa, Member of Commission 1 DPRD of North Minahasa Regency, Regional Secretary of North Minahasa, Assistant 1 of the Regional Secretariat of North Minahasa, Head of the Minut PMD Service, Minut Inspector, Head of ASN Transfer and Promotion at BKPSDM Minut, Head of PPEMKP at Minut PMD Service, Head of Regional Finance Subdivision at Minut Social Service, BUMDes Sector Analyst at Minut PMD Service, Head of Wori Subdistrict, Head of Budo Village, Head of Talawaan Atas Village, BUMDes administrators of Budo Village and Talawaan Atas Village, elements of the community/UMKM actors, and tourists from Budo Tourism Village . Based on the results of research in the field, it can be concluded that the Organizational Development of Village-Owned Enterprises has not been implemented optimally due to lack of availability of human resources, low budget, lack of community participation, lack of diversification of BUMDes business types, and lack of programs and activities related to BUMDes both in the Regional Government of North Minahasa Regency and Village government.